New derivatives of salicylamides: Preparation and antimicrobial activity against various bacterial species - Pauk, Karel; Zadražilová, Iveta; Imramovský, Aleš; Vinšová, Jarmila; Pokorná, Michaela; Masaříková, Martina; Cížek, Alois; Jampílek, Josef (Bioorganic & medicinal chemistry, 2013)
Three series of salicylanilides, esters of N-phenylsalicylamides and 2-hydroxy-N-[1-(2-hydroxyphenylamino)-1-oxoalkan-2-yl]benzamides, in total thirty target compounds were synthesized and characterized. The compounds were evaluated against seven bacterial and three mycobacterial strains. The antimicrobial activities of some compounds were comparable or higher than the standards ampicillin, ciprofloxacin or isoniazid. Derivatives 3f demonstrated high biological activity against Staphylococcus aureus (⩽0.03μmol/L), Mycobacterium marinum (⩽0.40μmol/L) and Mycobacterium kansasii (1.58μmol/L), 3g shows activity against Clostridium perfringens (⩽0.03μmol/L) and Bacillus cereus (0.09μmol/L), 3h against Pasteurella multocida (⩽0.03μmol/L) and M. kansasii (⩽0.43μmol/L), 3i against methicillin-resistant S. aureus and B. cereus (⩽0.03μmol/L). The structure-activity relationships are discussed for all the compounds.
Keywords: Microbial Sensitivity Tests; Antibacterial; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; salicylamidy; Salicylamides; Salicylamide derivatives; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; ciprofloxacin; ampicilin; Antimycobacterial; Ciprofloxacin; Gram-Negative Bacteria; grampozitivní bakterie; Ampicillin; Gram-Positive Bacteria; gramnegativní bakterie